Scrub typhus: A rare cause of secondary nephrotic syndrome - Ankur Singh; Akansha Anjali; Rajniti Prasad; Pradyot Prakash; Om Prakash Mishra (Journal of Vector Borne Diseases, 2021)
Scrub typhus is an important etiological agent in acute febrile illness in the post-monsoon season in tropical countries. It leads to dreaded complications if left untreated. Acute kidney injury is one such complication. Malaria, syphilis, and HIV have been associated with secondary nephrotic syndrome in pediatric age group. Scrub typhus has been reported only once with nephrotic syndrome. We report a case of scrub typhus-associated nephrotic syndrome with acute kidney injury in a five-year-old female with uneventful outcome